2012
DOI: 10.3389/fgene.2012.00100
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and Binding Sites of Human Transcription Factors

Abstract: Mutations in any genome may lead to phenotype characteristics that determine ability of an individual to cope with adaptation to environmental challenges. In studies of human biology, among the most interesting ones are phenotype characteristics that determine responses to drug treatments, response to infections, or predisposition to specific inherited diseases. Most of the research in this field has been focused on the studies of mutation effects on the final gene products, peptides, and their alterations. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Condition-specific binding preferences are an important biological property of certain TFs [45] . Polymorphisms and de novo mutations may also alter a sequence of a particular binding site complicating known-TFBS discovery [46] , [47] . Hence, we reasoned that certain ab initio MFs might reflect condition-driven, or protein complex-dependent, deviations from known TFBS models.…”
Section: Resultsmentioning
confidence: 99%
“…Condition-specific binding preferences are an important biological property of certain TFs [45] . Polymorphisms and de novo mutations may also alter a sequence of a particular binding site complicating known-TFBS discovery [46] , [47] . Hence, we reasoned that certain ab initio MFs might reflect condition-driven, or protein complex-dependent, deviations from known TFBS models.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors propose that variants found in coding regions (intragenic variants) have the greatest potential to be functionally important and more likely to contribute to trait variation [ 27 ]. Out of the variants annotated in intragenic regions, the splice site and synonymous classes are some of the most significant in our study, capturing a large proportion of the variance out of the total variance explained (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the precise locations of DNA sites binding transcription factors (TFs) is necessary to reconstruct regulatory networks ( 1 ), as well as to evaluate functional consequences of mutations in DNA regulatory regions ( 2 , 3 ) or interactions between DNA-bound TFs ( 4 ). Conventional methods that experimentally reveal nucleotides contacting regulatory proteins are low throughput, laborious and expensive ( 5 ).…”
Section: Introductionmentioning
confidence: 99%